ANALISIS PENERAPAN PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 TENTANG PAJAK PENGHASILAN USAHA MIKRO KECIL DAN MENENGAH DI KOTA PAREPARE - RIZKY ZULFIANSYAH; ASRUL HIDAYAT (Case Law : Journal of Law, 2026)
This study aims to determine the effectiveness of the implementation of Government Regulation No. 23 of 2018 on local revenue in Parepare City, and to determine the challenges faced in implementing Government Regulation No. 23 of 2018 in Parepare City. This research was conducted in Parepare through observation, literature review, and interviews. The research approach used by the author in this work is a normative-empirical approach. The source of information is the investigation of theoretical questions using primary, secondary, and tertiary data. The results of this study indicate that the implementation of Government Regulation No. 23 of 2018 concerning Income Tax on Income from Businesses Received or Obtained by Taxpayers with a Certain Gross Turnover in Parepare City has not been effective in increasing local revenue. This is because most micro, small, and medium enterprises (MSMEs) have not reached the turnover limit as stipulated in the regulation, so that not all MSMEs are subject to the obligation to pay tax. In addition, other challenges faced are the uncertain daily income fluctuations of MSME actors, as well as the weak system for recording and archiving income data. This condition results in a mismatch between the nominal tax paid and the actual turnover, and makes it difficult to determine tax obligations accurately in accordance with applicable provisions.